2003
DOI: 10.1302/0301-620x.85b2.13257
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density in long-term survivors of highly malignant osteosarcoma

Abstract: We studied the bone mineral density (BMD) of 48 long-term survivors of highly malignant osteosarcoma who had been treated according to the chemotherapy protocols of the German- Swiss-Austrian Co-operative Osteosarcoma Study Group which include high-dose methotrexate. The mean age of the patients was 31 +/- 4.2 years and the mean follow-up 16 +/- 2.2 years. The BMD of the lumbar spine and of the proximal femur of the non-operated side was measured by dual-energy x-ray absorptiometry. A questionnaire was given t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
96
0
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(104 citation statements)
references
References 20 publications
5
96
0
3
Order By: Relevance
“…58 The deficit in bone mineral may persist for more than a decade. 59 A similar deficit has been noted in survivors of rhabdomyosarcoma. 60 Although the usual treatment of such bone and soft tissue tumors includes multiagent chemotherapy, methotrexate and ifosfamide have been labeled as especially toxic to bone.…”
Section: Bone Mineral Loss and Cancer In Early Lifesupporting
confidence: 56%
“…58 The deficit in bone mineral may persist for more than a decade. 59 A similar deficit has been noted in survivors of rhabdomyosarcoma. 60 Although the usual treatment of such bone and soft tissue tumors includes multiagent chemotherapy, methotrexate and ifosfamide have been labeled as especially toxic to bone.…”
Section: Bone Mineral Loss and Cancer In Early Lifesupporting
confidence: 56%
“…HD-MTX, a standard agent in osteosarcoma protocols, reportedly has reduced BMD [8,17]. The literature, however, shows decreased BMD in patients with Ewing's sarcoma treated without HD-MTX [33].…”
Section: Discussionmentioning
confidence: 99%
“…MTX osteopathy was described in eight of 87 patients with osteosarcoma with at least three of four radiographic abnormalities including osteopenia, dense zones of provisional calcification, insufficiency fractures, and involvement of multiple bones [8]. Among 48 long-term survivors who had DEXA, 10 had osteoporosis, 21 had osteopenia, and 18 had fractures after chemotherapy [17]. However, Ruza et al questioned MTX as one of the most suspect chemotherapeutics causing premature bone loss because the BMD of patients with Ewing's sarcoma treated without MTX was reportedly decreased [33].…”
Section: Introductionmentioning
confidence: 99%
“…A follow-up of long-term survivors of highly malignant osteosarcoma who had received high-dose chemotherapy including cyclophosphamide showed that osteoporosis was a common occurrence in these patients. 40 Thus, besides immunosuppressive therapy, the myeloablative regimen before BMT may be responsible for the decreased bone mass in long-term survivors of BMT.…”
Section: Discussionmentioning
confidence: 99%